The effect of inhalation of essential oil from Rosmarinus officinalis on scopolamine‐induced Alzheimer's type dementia model mice. (15th January 2018) - Satou, Tadaaki; Hanashima, Yuki; Mizutani, Iho; Koike, Kazuo
Abstract: Essential oil from Rosmarinus officinalis (Rosemary essential oil, EORO) may improve cognitive function by activating the central nervous system. However, no scientific basis for the effect of EORO has been described. Therefore, we investigated the effect of EORO on Alzheimer's type dementia using model mice. Mice were administered EORO by inhalation. Then, scopolamine was used to prepare Alzheimer's type dementia model mice. To evaluate cognitive function, the Y‐maze test was used for assessment of short‐term memory. EORO produced a significant improvement in the rate of spontaneous alternation behavior. Furthermore, 1, 8‐cineole, α‐pinene, and β‐pinene, the main components of EORO, were detected in the brain in a concentration‐dependent manner following inhalation of EORO. Thus, inhalation of EORO may improve cognitive function in a model of Alzheimer's type dementia. Components such as 1, 8‐cineole and others are likely involved in the effects on the brain. Examination of the detailed mechanism of action of EORO is necessary for future clinical application. Abstract : Effect of rosemary essential oil on Alzheimer's dementia model mice by administration of scopolamine (2 mg/kg i.p.). spontaneous alternation behavior (%). Data are presented as the mean ± standard error ( n = 5) *** p <0.001. EORO 4 i.h.: inhaled administration of rosemary essential oil (4 μL/L air). Water i.h.: inhaled administration of water (negative control)